Խորհրդային Հայաստանից ադրբեջանական բնակչության վերաբնակեցումը 1947-1953 թթ. - Հովհաննիսյան, Գայանե Ս. (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
Цель данной статьи — представить процесс переселения азербайджанского населения из Советской Армении в 1948-1953 гг. Изучение архивных документов доказывает в высшей степени добровольный характер процевва переселения. The purpose of this article is to present the process of resettlement of the Azerbaijani population from Soviet Armenia in 1948-1953. An examination of the archival documents demonstrates the highly voluntary nature of resettlement process.
Keywords: Պատմություն; Հայկական Խորհրդային Սոցիալիստական Հանրապետություն; Ժողովրդագրություն; Միջազգային հարաբերություններ